Morphological Development of the Residential Unit in the Iraqi City (Fallujah City - Case Study) - Suleiman, Naba Ali; Ali , Bilal Bardan (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aims to determine the morphological development of the residential unit through its chronological stages and the extent to which this dynamic development is reflected in the urban style and street systems. Additionally, the study aims to prepare recommendations that support the preservation of traditional urban identity to maintain Arab culture in a way that suits the requirements of the Iraqi family. Methods: The study relies on analytical, deductive, and statistical approaches in presenting and analyzing the morphological development of the residential unit in the city of Fallujah. This was done through a field visit to support the research with data and information, analyzing them, and studying the qualitative and quantitative changes that occurred in modern residential units and street systems in accordance with the research objectives. Results: The study found that the qualitative and quantitative morphological development of residential units in the city of Fallujah is linked to its historical, economic, and social development. This is reflected in the type of urban style adopted during each period the city has passed through. Conclusion: The study traces the morphological development of the residential unit in Fallujah over three time periods closely related to the spatial, temporal, and environmental context. The study described the characteristics of the residential unit, leading to the developments that accompanied the city’s growth and evolution.